Economics of development and planning/ by A.N. Agrawal and Kundan Lal - "Agrawal, A . N." (New Delhi, 1989)
Highlights the trends and developments in the economy as well as the policy measures adopted by the Government to tackle them. This book equips the reader with the analytical tools for understanding the Indian economy, explains the economics of underdevelopment and development, and gives an overview of the state of the Indian economy.
Keywords: Economic